Effects of Genetic Polymorphisms of Drug Transporter ABCB1 (MDR1) and Cytochrome P450 Enzymes CYP2A6, CYP2B6 on Nicotine Addiction and Smoking Cessation - Muderrisoglu, Ahmet; Babaoglu, Elif; Korkmaz, Elif Tugce; Ongun, Mert C.; Karabulut, Erdem; Iskit, Alper B.; Emri, Salih; Babaoglu, Melih O. (Frontiers in Genetics, 2020)
Objectives: To determine the effects of genetic polymorphisms of ABCB1 (MDR1), CYP2A6, CYP2B6 on smoking status, and clinical outcomes of smoking cessation therapies in a Turkish population. Methods: 130 smokers and 130 non-smokers were recruited. Individuals who never smoked were described as non-smokers. 130 smokers were treated with nicotine replacement therapy (NRT) (n=40), bupropion (n= 47), bupropion + NRT (n= 15), and varenicline (n= 28). Smokers were checked by phone after 12 weeks of treatment whether they were able to quit smoking or not. Genotyping and phenotyping were performed. Results: Cessation rates were as follows; 20.0% for NRT, 29.8% for bupropion, 40.0% for bupropion + NRT, 57.1% for varenicline (p= 0.013). The frequency of ABCB1 1236TT-2677TT-3435TT haplotype was significantly higher in non-smokers as compared to smokers (21.5 % vs. 10.8, respectively; p= 0.018). Neither smoking status nor smoking cessation rates were associated with genetic variants of CYP2A6 (p= 0.652, p= 0.328, respectively), or variants of CYP2B6 (p = 0.514, p= 0.779, respectively). Conclusions: Genetic variants of the drug transporter ABCB1 and the 1236TT-2677TT-3435TT haplotype was significantly associated with non-smoking status. Neither ABCB1 nor CYP2A6, CYP2B6 genetic variants were associated with smoking cessation rates at the 12th week of drug treatment.